Διαφοροποίηση των παθότυπων του clobodera rostochiensis στην περιοχή Αυγόρου - Παναγιώτου, Μυριάνθη (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The potato cyst nematodes (PCN), Globodera rostochiensis (Woll) (Gr) and Globodera pallida Stone (Gp) are soil-borne pathogens that cause severe losses to the potato cultivation in Cyprus. In order to manage PCN with the use of resistant varieties, the identification of pathotypes of both species is necessary. In this study, the presence of PCN in the wider area of Augorou village was investigated, as well as the identification of pathotypes that are encountered in eight potato fields of the area. Soil samples were used for cyst extraction following the Fenwick method. Molecular characterization of cysts was performed by PCR reactions. The PCR products revealed the presence of G. rostochiensis alone, in all the soil samples tested. Pathotype identification was carried out using the Pathotype Scheme for the European pathotypes of PCN. In addition, Solanum plants were used as differential hosts, with a different degree of resistance to the pathotypes of G. rostochiensis: Solanum vernei VTn 62-33-3, Saturna, S. vernei G-LKS 58-1642-4, S.vernei 65-346/19 and S.vernei KTT 60- 21-19. Variety Spunta was used as a control. Pathotype identification results were evaluated based on the equation Pf / Pi, where Pf = final population and Pi = initial population of PCN. In the eight agricultural fileds of the wider area of Augorou village, G. rostochiensis Ro1 was identified as the only pathotype. This pathotype is common in the Kokkinochoria area where PCN are generally found. Management of Ro1 pathotype can be achieved through Integrated Pest Management (IPM) using resistant varieties with a high commercial value. However, the combined use of resistant varieties with nematicides is recommended in order to avoid the development of any other pathotype / species that might be more aggressive than Ro1.
Keywords: Potatoes; Vegetables -- Diseases and pests; Πατάτες; Λαχανικά -- Ασθένειες και παράσιτα